Aging Effects on the Mechanical Performance of Carbon Fiber-Reinforced Composites - Ayesha Afzal; Muhammad Kashif Bangash; Asif Hafeez; Khubab Shaker (International Journal of Polymer Science)
Carbon fiber-reinforced composite (CFRC) is a well-known hi-tech material with diverse applications. The CFRC faces several environmental conditions during its application, e.g., elevated temperatures, humidity, exposure to UV radiation, and acidic and alkaline environments. These environmental factors strongly affect the performance of CFRC, and they tend to age with time. Aging reduces the mechanical properties of the composite and ultimately its service life. In this review, the focus is on the aging of composite, common types of aging (thermal, hydrothermal acid and alkaline, and UV radiation), and the role of the third phase (fillers) in the aging process. There are numerous factors involved in the aging of composite. Aging starts with microcracks and proceeds towards delamination which further exposes the internal surface to environments. When the depths are exposed, free radicals are released and further deteriorate the internal structures. They create more pathways for oxygen to reach every millimeter of composite, thus reducing the mechanical performance of the composite. Usually, a trend is seen that introducing filler might slow down or compensate for the mechanical performance after aging. This trend is explored in the review article. However, usually, the third phase remained neutral and sometimes reduced and/or enhanced the mechanical properties after aging. In thermal aging, different metallic oxides have a noteworthy effect on mechanical performance. The synergistic effect of the third phase and aging on CFRC mechanical performance is also tabulated.